Guided Imagery Intervention to Reduce Anxiety in Nursing Home Elderly Resident - Kurniati, Safra Ria; Putri, Mawar Eka (Universitas Airlangga, 2022)
Introduction: The increasing number of the elderly population will cause health problems in the elderly, including mental health problems. However, study of anxiety in elderly is limited. Seeing the conditions experienced by the elderly, it is very necessary to pay attention and to provide intensive mental guidance which is then studied, internalized and practiced by the elderly in daily life. This study aims to determine the effect of guided imagination techniques on elderly anxiety. Method: The research design was a pre-experimental pre and post test design with 30 elderly respondents. Sample was chosen by purposive sampling technique. Data were collected by using Hamilton Anxiety Rating Scale. Results: After the intervention, it was found that guided imagination had an effect on the anxiety score of the elderly. Conclusions: This study concludes that guided imagery can be applied to create a relaxation effect to elderly, thus will have an impact on anxiety level.